Examen Especial al Activo Corriente de la Empresa de Aluminio y Vidrio de la señora Calderón Camacho Mélida Angelita de la ciudad de Loja. Periodo 2021. - Rueda Rueda, José Luis (2023)
This Curricular Integration Work is called: “SPECIAL EXAMINATION OF THECURRENT ASSETS OF THE ALUMINUM AND GLASS COMPANY OF MRS. CALDERON CAMACHO MELIDA ANGELITA OF THE CITY OF LOJA. 2021 PERIOD”, was prepared in accordance with the provisions of the Internal Control Standards, International Accounting Standards, Generally Accepted Auditing Standards and Generally Accepted Accounting Principles. The special examination process was carried out starting with planning, which includes preliminary planning, which includes general information about the company and the main activities it carries out, and specific planning that allows for the evaluation, rating the company's level of risk and confidence; at the implementation stage, taking into account the components identified for the analysis, applying tests and procedures to accounting records, in order to obtain sufficient evidence, competent and pertinent to prepare the report containing the results, in which the respective comments are presented, conclusions and recommendations, specifying compliance with the rules, principles and provisions governing the company, identifying existing shortcomings and proposing possible solutions so that, if deemed necessary, the manager can apply them in a timely manner for the improvement of the company. Concluding that, when evaluating the internal control system implemented to the Current Asset accounts, it was determined that there is a low level of risk and a high level of confidence, due to the absence of a manual of policies and proceduresspecifying instructions, responsibilities and information about the different operations or economic activities carried out by the company, and allowed to determine that there are no significant irregularities affecting the reasonableness of the balances presented in the Financial Statements for the year 2021.